Inside Cover: A Sodalite‐Type Silver Orthophosphate Cluster in a Globular Silver Nanocluster (Angew. Chem. Int. Ed. 31/2020). Issue 31 (4th June 2020) - Deng, Chenglong; Sun, Cunfa; Wang, Zhi; Tao, Yunwen; Chen, Yilin; Lin, Jinqing; Luo, Genggeng; Lin, Bizhou; Sun, Di; Zheng, Lansun
Abstract : A silver orthophosphate cluster (SOC) can be stabilized in the cavity of a giant silver nanocluster. In their Communication on page 12659, G. Luo, D. Sun, and co‐workers present a multi‐shell 102‐silver nanocluster in which a rare rhombicosidodecahedral 60‐silver nanocluster accommodates an unprecedented sodalite‐type SOC {(Ag3 PO4 )8 } concomitantly encapsulating an octahedral Ag6 core. This study is the first presentation of the SOC concept.